Teaching in conflict contexts: dimensions of subjective wellbeing in Palestinian teachers living in Israel and the occupied Palestinian territory. (21st February 2018) - Pepe, Alessandro; Addimando, Loredana; Dagdouke, Jamal; Yagi, Shaher; Veronese, Guido
Abstract: Background: Subjective wellbeing can be defined in terms of good mental state, including positive and negative evaluations that people make of their affect and lives. The aim of this study was to identify specific domains of wellbeing that are salient to Palestinian teachers living in three different contexts (West Bank, Gaza Strip, and Israel) and to map how components of subjective wellbeing vary between the three cohorts. Methods: Data were gathered from interviews of teachers participating in 16 focus groups and from 36 key informants (including psychologists, counsellors, school principals, lawyers). Participants were divided into three groups according to their working locations. Data were analysed by using a mixed-method approach. We used thematic textual analysis, and data were cross-validated with results of statistical significance of lexical specificities (ie, domain-specific terms extracted from specific participants' lexicon) and semantic network analysis. Findings: We interviewed 104 teachers. First-order hierarchical categorisation of thematic analysis revealed four dimensions of subjective wellbeing: psychosocial, professional-related, economic issues, and contextual factors. Some second-order subcategories were quality of teaching work, personality aspects, emotional dimensions, political dimensions, and psychological dimensions. Analysis of lexical specificities and results of semantic network analysis revealed that the importance of different components of subjective wellbeing varied across geographical cohorts. Overall, the results of qualitative and quantitative data analysis showed a clear relationship between the teachers' subjective wellbeing and the places they lived. Interpretation: General themes were common in all populations, but the three cohorts differed in terms of the relative salience of each theme. The prominent themes for the Gazan group were quality of teaching, social dimensions, and religion. The key themes for the West Bank group were economic, social dimensions, and recognition. Salient themes for the Arab-Israeli group were professional, emotional, and social dimensions. Despite some differences between the diasporic Palestinian populations in the occupied Palestinian territories and Israel, the categories of wellbeing are supported in all cohorts. Funding: None.